Marital economies: A comparative class study in two contemporary Cairo neighborhoods - Mohammad, Sahar Mohsen (AUC Knowledge Fountain, 2018)
This thesis topic emerged out of my own personal experience. When my daughter engaged many questions came to my mind, such as what is the criterion upon which "our family" and the groom's family will run the marital expenditures needed for them to start their new life. As it was the first experience to my family I started to discuss this matter with people who belong to my community and who had experiences in that regard to benefit from their past experiences. I primarily noticed that their marital monetary decisions are not identical. Then, I started to widen my discussion to include different social segments; the disparities between their choices was not based only on their different socioeconomic circumstances as I thought. As there were various opinions and beliefs between the older and younger members in the one family. I also noticed that when people make specific choices regarding marital economic imperatives they not only aim to purchase the material function of the commodity, but they portray and represent themselves according to the self-image they previously have or aim to become. Which obviously appear in the different patterns of consumption they practice. Exploring the driving forces that control their choices was what ignited my curiosity as a researcher. While the process of establishing a new family consists of different social, economic and cultural elements, it was important to problematize my study within the dominant socio-economic and cultural climate in the Egyptian context, which is characterized by the implementation of neoliberal economic policies. In addition to consumption culture that led to the commodification of everything including marriage. My thesis has attempted to fill a research gap through looking at how new subjectivities are made and remade in two economically and socially distinct areas; Ain-Shams and Al-Rehab city. This is a novelty because most (if not all) ethnographies conducted on the Egyptian household tend to focus on lower income communities. The research enhances the debates in the field by examining the shifts in "marital imperatives" patterns of consumption among the different segments of the middle-class Egyptians after 2011th revolution, with a particular focus on how these modes of consumption in addition to self- commodification work to constitute new socioeconomic subjectivities and status distinctions in changing urban spaces. This specific focus represents another novelty in my thesis. While the research focusses on the disparate modes of consuming marital imperatives I argue that consumption practices in Egypt deserve more scholarly attention than they have received. This research could be a foundational read for future researchers interested in the topic and many fruitful future research questions can be found in its pages. For example, it may interest those working on urban space, youth, and the social consequences of economic transformation; in addition to urban redistribution in contemporary Egypt. The ethnographic research methodology was my primary method of collecting data, participant observation and face-to-face interaction with my interlocutors facilitates my attempt to explore how individuals in the two assigned neighborhoods construct, reconstruct and display new subjectivities under the logic of commodification. In other words, it helped me to touch the actuality of the theoretical framework of my thesis. I have accomplished a comprehensive insight about the way in which the commodification of marriage as a part of the commodification of all walks of life under neoliberalism and capitalist economy affects the process of selfsubjectification through two possible mechanisms. first by self-understanding which is mediated by consuming marital imperatives that holds specific social images. In this sense, self-definition depends on the appropriation of the traits of commodities. We know who we are, we judge the quality of our inner experience and we represent ourselves through identification with the things we buy. Second by self-commodification that involves the reorganization of our personal lives and relationships on the model of market relations. This adaptation is well illustrated by the recent practice of "personal branding" a strategy of cultivating a name and image of ourselves that we manipulate for economic gains. In my research I had presented several examples of self- branding within the economics of marriage. Both meanings of self-commodification concern the terms in which we define and display ourselves and our well-being. Money is at the heart of the construction of new subjectivity within the economics of marriage. On the one hand, it is needed for purchasing marital imperatives and on the other hand it is the main destination for selfcommodification and obtaining independence especially for the young generations who are suffering from the longevity of dependency on their families. Which negatively affects their freedom to choose their priorities in spending the cost of marriage. The precarious state of being within the Egyptian neoliberal context has been expanded to contain different social segments such as well-educated young generations which forced a great number of them to invest in themselves; the individuals are constituted as subjects of "human capital". In sum, some of the motivations that lead the economic choices among Al-Rehab residents was the lifestyle and peer and social pressure while for Ain Shams inhabitants were money, traditions and showing off.